1984
DOI: 10.1128/aac.26.4.527
|View full text |Cite
|
Sign up to set email alerts
|

Itraconazole, a new triazole that is orally active in aspergillosis

Abstract: Itraconazole is a new orally active triazole derivative with broad-spectrum antifungal activity. This drug is effective in experimental aspergillosis and possesses in vitro activity against various species and strains of Aspergillus. Morphological destruction of inoculated hyphae and complete inhibition of hyphal outgrowth in culture is obtained from 0.07 micrograms ml-1 (10(-7)M) onward. These properties make itraconazole a likely candidate for clinical evaluation in disseminated aspergillosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(62 citation statements)
references
References 16 publications
3
59
0
Order By: Relevance
“…Oral administration of itraconazole to mice with experimental acute, systemic aspergillosis prolonged the survival of the animals and cleared the fungus from the organs of 6 of 30 of the mice. Graybill and Ahrens (111) confirmed the observations of Van Cutsem et al (321) in a mouse model. These investigators noted, however, that amphotericin B was more effective than itraconazole in prolonging survival in infected/treated mice.…”
Section: Antifungal Imidazoles Under Developmentsupporting
confidence: 80%
See 1 more Smart Citation
“…Oral administration of itraconazole to mice with experimental acute, systemic aspergillosis prolonged the survival of the animals and cleared the fungus from the organs of 6 of 30 of the mice. Graybill and Ahrens (111) confirmed the observations of Van Cutsem et al (321) in a mouse model. These investigators noted, however, that amphotericin B was more effective than itraconazole in prolonging survival in infected/treated mice.…”
Section: Antifungal Imidazoles Under Developmentsupporting
confidence: 80%
“…Van Cutsem et al (321) first reported the activity of itraconazole against experimental aspergillosis. Oral administration of itraconazole to mice with experimental acute, systemic aspergillosis prolonged the survival of the animals and cleared the fungus from the organs of 6 of 30 of the mice.…”
Section: Antifungal Imidazoles Under Developmentmentioning
confidence: 99%
“…The azole class of antifungal agents offers two possible alternatives. Itraconazole, a nitrogen-substituted triazole, has been found to be active in vitro against several species of Aspergillus [36,37]. In vivo evaluation with use of a murine model revealed greater activity than that achieved by ketoconazole, but no comparison was made with the activity of amphotericin B [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Itraconazole, a nitrogen-substituted triazole, has been found to be active in vitro against several species of Aspergillus [36,37]. In vivo evaluation with use of a murine model revealed greater activity than that achieved by ketoconazole, but no comparison was made with the activity of amphotericin B [37,38]. It is unfortunate that only a limited number of case repons have described the use of itraconazole for the treatment of aspeg illosis in humans, with variable results [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Recently we have shown that cyclosporin A, a lipophilic agent that partitions between plasma membranes, reverses multidrug resistance both in vitro and in vivo (5,6). Itraconazole, a new generation 1,2,4 triazole antifungal agent that inhibits different cytochrome P-450 systems (7)(8)(9), has been shown to synergize with cyclosporin A (10). Therefore, we set out to explore the possibility of whether similar synergism would exist between these two compounds in reversing MDR in vitro.…”
Section: Introductionmentioning
confidence: 99%